The birth of the modern world, 1780-1914 global connections and comparisons - Bayly, Christopher Alan 1945-2015 (Blackwell Publishing, 2004)
From the Publisher: This thematic history of the world from 1780 to the onset of the First World War reveals that the world was far more 'globalised' at this time than is commonly thought. Explores previously neglected sets of connections in world history. Reveals that the world was far more 'globalised', even at the beginning of this period, than is commonly thought. Sketches the 'ripple effects' of world crises such as the European revolutions and the American Civil War. Shows how events in Asia, Africa and South America impacted on the world as a whole. Considers the great themes of the nineteenth-century world, including the rise of the modern state, industrialisation and liberalism. Challenges and complements the regional and national approaches which have traditionally dominated history teaching and writing.
Includes bibliographical references and index
Keywords: Geschichte 1700-1800; Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1780-1914; Weltgeschichte 1780-1914; Histoire - 19e siècle; Histoire - 20e siècle; Imperialisme; Moderniteit; Mondialisation; Natievorming; Révolutions - Histoire - 18e siècle; Wereldgeschiedenis; Geschichte; Globalisierung; Revolutions -- History -- 18th century; History, Modern -- 19th century; History, Modern -- 20th century; Globalization; Weltgeschichte